Discussion on the Value of Wind-induced Vibration Coefficient of Independent Steel Tube Lightning Rod Structure Design. Issue 3 (August 2019) - Huang, Zhenxing; Zhou, Mei
Abstract: This study compared the reliability of the ISTLRs (independent steel tube lightning rod) whose structure was designed using WIVC (wind-induced vibration coefficient) in DL/T 5457-2012, GB50009-2012 and AR method. Based on the assembly diagram of the lightning rod in the lightning rod replacement project in a 220kV substation, the finite element model was established in ANSYS Workbench. The three WIVCs were substituted into the HD (horizontal displacement) of the structure design, and the reliability of structure designed from the three was compared. Suggestions were made on the value of the WIVC when designing an ISTLR structure.